BERBAGAI JENIS PUPUK KANDANG SEBAGAI PENUNJANG PERTUMBUHAN BIBIT SIRSAK (Annona muricata Linn) (Various Types Of Fertilizers As Supporting The Growth Of Sirsak (Annona Muricata Linn)) - Ananto Ananto; Syaifuddin Islami (Fakultas Pertanian Universitas Tamansiswa Padang, 2018)
This study was prepared based on Completely Randomized Design (RAL) with four treatment levels and three replications. The observed data were analyzed by using F test at 5% real level and if F value count> F table 5%, then continued with Duncens New Multiple Range Test (DNMRT) test at 5% real level. The treatment given are: A = Control (without manure), B = soil + cow manure, C = soil + goat manure, D = soil + chicken manure. The variables observed were seed height, leaf number, leaf width, leaf length, root length of the rider, stem circumference and percentage of live seedlings. The result of the research showed that the effect of chicken manure showed a significant effect on the seed height of 5.69 cm, the number of leaves was 8.83, the leaf width was 0.74 cm, the length of the leaf was 1.64 cm, the root length of the root was 8, 61 cm and stem circumference of 0.35 cm.